2021
DOI: 10.3390/brainsci11091175
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms among Individuals Hospitalized with COVID-19: Three-Month Follow-Up

Abstract: Individuals affected by Coronavirus Disease 2019 (COVID-19) may experience psychiatric symptoms, including depression and suicidal ideation, that could lead to chronic impairment and a reduction in quality of life. Specifically, depressive disorder shows high incidence and may lead to chronic impairment and a reduction in the quality of life. To date, no studies on the presence of suicidality and quantitative analysis of depressive symptoms and their risk factors have yet been published. In this study, we aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…As shown in Figure 1 , from 2078 records screened on title and abstract, 114 full texts were analyzed. The review process led to the selection of 33 studies ( 3 , 4 , 6 8 , 14 41 ). These studies, referring to 33 different samples and involving a total of 282,711 LC participants, were included in the final selection and quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1 , from 2078 records screened on title and abstract, 114 full texts were analyzed. The review process led to the selection of 33 studies ( 3 , 4 , 6 8 , 14 41 ). These studies, referring to 33 different samples and involving a total of 282,711 LC participants, were included in the final selection and quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the long-term effects of lockdown and social isolation policies for mental health, mainly in regards to depression and anxiety, are still an open question. Currently available studies report a 15% prevalence of depressive symptoms 76 and a 19% prevalence of post-traumatic stress disorder (PTSD) (10.4% overt, 8.6% subclinical) 77 at three months post-discharge. At present it is expected that rates of PTSD, anxiety and depression will increase 78 for COVID long haulers, although symptoms are supposed to improve over time 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 .…”
Section: Resultsmentioning
confidence: 99%
“…People who are admitted to ICUs may already have or not have psychological distress; ICU admission may worsen pre-existing psychological distressed, expressed as a variety of psychiatric symptoms which resemble post-traumatic stress disorder (PTSD), depression, excessive worrying, insomnia, and anxiety, or may induce newly developed psychological distress. An Italian study found that ICU admission may be associated with increased depression levels and suicidal ideation in a small, but clinically significant proportion of patients with COVID-19, and may worsen pre-existing depression[ 27 ]. A Turkish study showed depression may be mediated by restricted visits to the ICU patient, while anxiety was mediated by ICU admission itself[ 28 ].…”
Section: Discussionmentioning
confidence: 99%